A solution-processed n-doped fullerene cathode interfacial layer for efficient and stable large-area perovskite solar cells. Issue 2 (14th December 2015) - Chang, Chih-Yu; Huang, Wen-Kuan; Chang, Yu-Chia; Lee, Kuan-Ting; Chen, Chin-Ti
Abstract : A facile and effective approach to enhance the performance and stability of perovskite solar cells is proposed by using a solution-processed cetyltrimethylammonium bromide (CTAB)-doped [6, 6]-phenyl-C61 -butyric acid methyl ester (PC61 BM) film as a cathode interfacial layer. Abstract : A novel solution-processed cetyltrimethylammonium bromide (CTAB)-doped [6, 6]-phenyl-C61 -butyric acid methyl ester (PC61 BM) film prepared by an extremely facile method is demonstrated as an effective cathode interfacial layer for perovskite solar cells (PSCs). Our results indicate that efficient doping takes place via anion-induced electron transfer between the bromide anions (Br − ) on CTAB and PC61 BM in the solid state, leading to a dramatic increase in electrical conductivity by more than five orders of magnitude. In addition, the CTAB-doped PC61 BM layer is capable of turning a more air-stable, high work-function (WF) Ag layer into an efficient low WF electrode as a result of the formation of favorable interfacial dipoles between Ag and the active layer. These characteristics enable the CTAB-doped PC61 BM layer to function as both an electron transport layer and a cathode buffer layer (CBL) in PSCs, thus simplifying the manufacturing process. This doped layer also exerts multi-positive effects for use in PSCs, including efficient interfacial charge transfer ability, superior charge selectivity, good film coverage on the perovskite layer, relatively weak thickness-dependent performance properties, general applicability to different perovskite materials, and good ambient stability. With this n-doped PC61 BM layer, the device delivers a high power conversion efficiency (PCE) up to 17.11%, which is superior to those of the devices with undoped PC61 BM layers (2.15%) and state-of-the-art CBL ZnO nanoparticles (10.45%). The application of the CTAB-doped PC61 BM layer in large-area solar cells (active area = 1.2 cm 2 ) is also demonstrated, and a remarkable PCE of 15.42% is achieved, which represents one of the highest PCE values for PSCs with a similar active area. More significantly, the resulting devices possess good ambient stability without the need for rigorous encapsulation.